The Effect of PVA and PEG Infusion on Titania Antibacterial Coating. (August 2019) - Margaretta, D O; Permadi, K W; Rahman, D Y; Utami, F D; Viridi, S; Abdullah, M
Abstract: Indonesia has great potential of the Solar energy, irradiated by the Sun throughout the years. Cotton textiles antibacterial has been prepared by coating Titania (TiO2 ) with Polyethylene glycol (PEG) and Polyvinyl alcohol (PVA) as adhesives. The method of depositing cotton using a simple dip coating. Cotton dry for 15 minutes with a halogen lamp, after the deposition process. Then, we do the antibacterial activity test using Plate Count Method. As a result, the coated cotton textiles with Polyvinyl alcohol (PVA), Polyethylene glycol (PEG) has antibacterial properties. Characterization by the Attenuated Total Reflectance (ATR) obtained that Titania (TiO2 ) surely adhere on the sample. From Attenuated Total Reflectance (ATR) characterization we conclude that Polyvinyl alcohol (PVA) and Polyethylene glycol (PEG) is not affecting the antibacterial ability of Titania (TiO2 ). But the infusion of Polyvinyl alcohol (PVA) and Polyethylene glycol (PEG) on Cotton increases the stiffness value of Cotton.